Evaluating the Impact of Business Intelligence on Enhancing Innovation in the Insurance Industry Considering the Role of Network Learning - Fatan , Behgol; Keramati, Mohammad Ali; Amin Mousavi , Seyed Abdollah (Business, Marketing, and Finance Open, 2024)
In today’s competitive business world, Business Intelligence (BI) serves as a key tool for data extraction and analysis, playing a crucial role in enhancing organizational innovation. This study aims to evaluate the impact of Business Intelligence on improving innovation in the insurance industry, considering the role of network learning. The research method is descriptive and survey-based. The statistical population consists of managers from various departments within the insurance industry. Data collection was conducted through field research using a questionnaire, employing a convenience sampling method. Structural equation modeling (SEM) with the partial least squares (PLS) approach was used for data analysis, utilizing the SMART PLS3 software. The research findings indicate that Business Intelligence has a significant positive effect on innovation, and network learning acts as a mediating factor that strengthens this effect. Additionally, the results suggest that innovation directly and indirectly influences organizational performance, and organizations that leverage Business Intelligence capabilities benefit from greater innovative advantages. The study's recommendations include investing in Business Intelligence systems, promoting a data-driven culture, developing network learning, integrating BI with modern technologies (such as artificial intelligence and machine learning), and optimizing innovation strategies. This research can assist organizations in making better strategic decisions and enhancing their competitive advantage.